ANALISIS PRAKTIKALITAS BUKU PANDUAN PENGGUNAAN DAN PERAWATAN KULIT ALAT LITSRIK PADA MAHASISWA PENDIDIKAN TATA RIAS - Putri, Mutia Putri; Asrah Rizki Fauzani; Putri Chairina Zulfiani (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2025)
The use of electrical tools in skin care practices requires a proper understanding of their functions, working procedures, and correct usage steps. However, some students still face difficulties in operating and maintaining the tools due to the lack of practical written guidance. This study aims to evaluate the practicality of an e-book guide designed as a supplementary learning medium. The e-book contains comprehensive information on the use and maintenance of electrical tools, expected to help students understand the course material independently. The research used a descriptive quantitative method with a Likert scale questionnaire as the data collection tool. The participants were 43 third-semester students from the 2023 cohort. The assessment covered aspects such as clarity, content structure, ease of understanding, and usefulness. Results showed that the e-book is practical, with 8.6% rating it fairly practical, 51.6% practical, and 39.8% very practical. The guide is considered appropriate and should be improved based on student feedback.